Ye Berlyn tapestrie : John Hassall's satirical First World War panorama - Hassall, John (Bodleian Library, 2014)
First published in 1915. - "Ye Berlyn Tapestrie" was created by pioneering illustrator John Hassall as a light-hearted reaction to the public outrage and anti-German propaganda following Kaiser Wilhelm's invasion of neutral Belgium on 4 August 1914. Parodying the most well-known pictorial representation of a foreign invasion, the eleventh-century Bayeux Tapestry, Hassall illustrated thirty cartoon panels that poke fun at the invaders and their 'frightfulness'. - In mock-archaic language he narrates the progress of the German army, never missing an opportunity to lampoon 'bad' behaviour: 'Wilhelm giveth orders for frightfulness.' The caricatured Germans loot homes, make gas from Limburg cheese and sauerkraut, drink copious amounts of wine and shamefully march through Luxembourg with 'women and children in front.' With comic inventiveness Hassall adapts the borders of the original to illustrate the stereotypical objects with which the English then associated their enemy: they are decorated with schnitzel, sausages, pilsner, wine corks and wild boar. - This form of satire is a very British response to war, in which humour becomes a principal tool of propaganda. While John Hassall was not employed by the Government of the day, his wonderfully comic creation taps into the British tradition of cutting the enemy down to size through satirising them. - Together with an introduction which sets out the historical background to the events described in the Tapestrie, every page of this rarely-seen publication is reproduced in this new edition in a fold-out concertina, just like the original, to resemble the style of the Bayeux Tapestry. When it is fully open it measures 525cm